Cidades de papel: representações fundiária de Belo Horizonte - a produção jurídica do espaço urbano e a irregularidade fundiária - Clara Cirqueira de Souza (2021)
This dissertation addresses the land tenure regularization in Belo Horizonte, MG, assessing how the legal technique affects the production of urban space. The approached problem derives from the justification, which arises of the federal executive, concerning the urgency of changing the land tenure rules as a way of guaranteeing the exercise of citizenship. The research has, as its theoretical framework, the theory of space by Henri Lefebvre, presented in the books The production of space and Space and politics – the right to the city II, aligned with the critique of urban planning formulated by Ermínia Maricato in The ideas out of place and the place outside of ideas and the theory on the political economy of the space by Milton Santos, shown in The Divided Space. Bearing in mind the understanding that the urban space is produced by the social practice put into everyday life, literary works, chronicles, and reports are brought to illustrate the other actors involved in space production. Initially, a normative and social-historical survey on the land issue in Brazil is presented, with a focus on urban land. This chapter also portrays the construction of Belo Horizonte to outline how the land matrix was historically formatted. For exposing the land matrix of Belo Horizonte, data was collected on municipal territorial management, using the 'BHMap' tool and data obtained, under the Access to Information Law (LAI), with the public agencies. These data come from the Municipal Technical Registry (CTM), Buildings and Typology of Use and Occupation parameterized by cartographic sector; Registry of Approved Plants (CP); Real Estate Registry (IC); Addressing by tax zone and notary district; and, finally, Addressing and Population Household and Neighbourhood, by popular neighbourhood. Notary data were also collected through the LAI with the 4th Office of Real Estate Registry of Belo Horizonte. The obtained data allowed, after being related, quantified, and consolidated, to demonstrate the lack of integration and technical cooperation between the responsible entities, as well as their disparity in territorial management and inspection of land regularity in the municipality. Finally, it is discussed whether the legal technique would be, in urban practice, directed to the promotion of social justice, as provided for in the Constitutional Urban Policy. For this purpose, it is analysed, based on the survey data, the effectiveness of the rule, and what jurisdictional protection is done from the dogmatic. As a final consideration, a legal urban order, consolidated solely in defence of the real estate property registration, is an instrument for the maintenance of urban poverty.